From garden to pickle - Nelson, Penelope, 1994- (2021)
"In From Garden to Pickle, early fluent readers learn how a pickle is made, from a cucumber growing to it being cut, brined, and jarred. Vibrant, full-color photos and carefully leveled text will engage young readers as they learn about how this food gets to their tables. An infographic illustrates the cycle with real photos and descriptions. From Garden to Pickle also features reading tips for teachers and parents, a table of contents, a glossary, and an index"--
"Bullfrog Books are published by Jump!"
Includes index.
Ages 5-8.
Keywords: Pickles -- Juvenile literature; Cucumbers -- Preservation -- Juvenile literature; Canning and preserving -- Juvenile literature